Taqwīm Kitāb al-Lugah al-‘Arabiyyah li al-Mustawā al-Ibtidāiyyah bimarkaz Ansyiṭah al-Ta’allum al-Mujtamaī Tahfaẓ al-Tamām Pekanbārū - Wijayanti, Ida; Promadi, Promadi; Masrun, Masrun (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This study aims to evaluate Arabic textbooks for Class 3 PKBM At Tamam Pekanbaru. This research is qualitative and uses a literature study approach. Data is the Arabic language book for grade 3 elementary school written by Ummu Munibah and published by Attuqa in 2022, according to Rusdy Ahmad Thuaimah. The data collection technique is documentation. Meanwhile, data analysis uses content analysis. The results of the study: (1) Arabic textbooks for Class 3 PKBM At Tamam Pekanbaru are suitable for use but only meet some of the standards for learning Arabic for foreign speakers in terms of material, culture, and education. (2) The content of Arabic textbooks for Class 3 PKBM At Tamam Pekanbaru has met the standards and principles of compiling good books for foreign speakers to learn Arabic. (3) Evaluation score: The researcher found a score suitable for using the book, with a valid value of 70 out of 85 and a percentage of 82.35%. Therefore, this book is suitable in the sense that the indicators for evaluating an Arabic language textbook are available in this book. However, some items are still lacking.